Natural enemies of Coelomera lanio (Coleoptera: Chrysomelidae) in the region of Viçosa, Minas Gerais, Brazil - Silveira, Rodrigo D (2002)
Coelomera lanio (Coleoptera: Chrysomelidae) is the most important defoliator of Cecropia trees. Natural enemies of C. lanio collected in the region of Viçosa, State of Minas Gerais, Brazil were identified on field observations in a forest fragment and on laboratory analyses. Individuals of C. lanio were not found on Cecropia pachystachya trees colonized by Azteca mülleri (Hymenoptera: Formicidae). The majority of the egg masses of C. lanio collected in the field were found to be parasitised by a species of the family Eulophidae (Hymenoptera), while larvae of this pest were attacked by a parasitoid of the family Tachinidae (Diptera). Individuals of Oplomus catena (Heteroptera: Pentatomidae) were observed preying on C. lanio larvae. The fungus Beauveria bassiana was found growing on larvae, pupae and adults of C. lanio while the fungus Metarhizium anisopliae only affected pupae of this insect in laboratory conditions